Pengaruh Profitabilitas, Likuiditas dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Makanan dan Minuman yang Terdaftar di BEI - M Khoirul Aziz; Riskin Hidayat (Otonomi, 2023)
This study aims to prove the effect of profitability, liquidity and capital structure on company value in food and beverage companies on the Indonesia Stock Exchange for the 2018-2021 period. This study uses the dependent variable company value, while the independent variables are profitability, liquidity and capital structure. The population used is 30 food and beverage companies on the Indonesia Stock Exchange for the 2018-2021 period. Data collection techniques in research conducted using the documentation method. While the selection of samples using purposive sampling method. The research sample consisted of 14 companies with 56 observations. The data analysis technique used was multiple linear analysis techniques. Before the previous regression was tested with the classical assumption test to obtain the Best Linear Unbias Estimate (BLUE) data. Based on the results of hypothesis testing, it shows that profitability has a significant positive effect, while liquidity has a no significant negative effect on company value. Capital structure has no significant positive effect on company value.